2013
DOI: 10.1159/000347034
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Allergenic Components from German Cockroach Fecal Extract by a Proteomic Approach

Abstract: Background: Cockroaches produce potent allergens, and cockroach feces are known to be especially rich in allergens. In this study, we analyze the allergenic components from cockroach feces and evaluate allergenicity of recombinant α-amylase identified from fecal extract. Methods: IgE-reactive proteins from German cockroach fecal extract were analyzed by proteomic analysis and immunoblotting. Recombinant α-amylase was produced and its allergenicity was evaluated by ELISA. Results: Analysis of German cockroach f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 19 publications
(20 reference statements)
0
37
0
Order By: Relevance
“…Since reviewed in 2014 [5,59], molecular studies have unveiled new structural features of allergens in groups 1, 2 and 5, and two new groups (11 and 12) have been added to the list. In addition to these officially recognized cockroach allergens, other potential allergens have also been identified that need further study [60–63]. This section will describe the twelve official groups of cockroach allergens with emphasis on new studies performed in the last 5 years.…”
Section: Cockroach Allergens: a Heterogeneous Group Of Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since reviewed in 2014 [5,59], molecular studies have unveiled new structural features of allergens in groups 1, 2 and 5, and two new groups (11 and 12) have been added to the list. In addition to these officially recognized cockroach allergens, other potential allergens have also been identified that need further study [60–63]. This section will describe the twelve official groups of cockroach allergens with emphasis on new studies performed in the last 5 years.…”
Section: Cockroach Allergens: a Heterogeneous Group Of Proteinsmentioning
confidence: 99%
“…First, recombinant Bla g 11 inhibited 55% of specific IgE to German cockroach whole-body extract among patients in Korea [63]. Second, the prevalence of IgE reactivity to group 11 allergens is high for certain populations: 1) Bla g 11 was recognized by 41.4% (12/29) of German cockroach sensitized subjects in Korea [63], and 2) a large proportion of Chinese cockroach allergic patients recognized natural Per a 11 purified from midgut of cockroaches using immunoblots (83%; 39/47) and skin prick test (80%; 12/15) [111]. Finally, Bla g 11 was immunodominant regarding T cell responses in asthmatic subjects, together with Bla g 5 and Bla g 9 ●[106].…”
Section: Cockroach Allergens: a Heterogeneous Group Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…2, Table 1). Amylase was also identified as an important allergen in German cockroach fecal extract 20. An interesting finding of fecal extract analysis is the IgE reactivity of various digestive enzymes, such as α-amylase, trypsin, chymotrypsin, metalloprotease, and midgut carboxypeptidase A.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of International Archives of Allergy and Immunology , Jeong and colleagues (14), from Korea, have used a proteomics approach to identify novel cockroach allergens in a B. germanica fecal extract. As it could be predicted, they have found that four of 12 IgE binding proteins were digestive enzymes including midgut carboxy peptidase A, chymotrypsin, astacin-like metalloprotease and trypsin.…”
mentioning
confidence: 99%